The role of beta-adrenolytic drugs in treating anxiety disorders - Brudkowska, Żaneta; Tomczyk, Małgorzata; Jusiak, Katarzyna; Karakuła-Juchnowicz, Hanna; Rudnicka-Drożak, Ewa (Current Problems of Psychiatry, 2025)
Introduction. Beta blockers are mainly used in treating cardiovascular diseases. However, it has been observed that these drugs have also an anxiolytic potential. Over the years, a number of clinical trials have been conducted aimed at determining the effectiveness of beta blockers in treating anxiety disorders. The aim. The main objective of the article is to present the significance and position of adrenolytic drugs in the pharmacotherapy of anxiety disorders on the basis of available literature. Moreover, the authors also decided to take into account the data from current research results, considering the problem of side effects of using adrenolytic drugs - especially the controversial reports on their effect on the development of affective disorders. Method. An analysis was conducted of articles from Medline/PubMed database, selected on the basis of the following key words: anxiety disorders, beta blockers, adrenolytic drugs, as well as on the basis of their dates of publication: 1960-2017. In order to conduct a reliable and complete review of literature, the authors decided to include works from quite an extended period of time. The articles included in the review were published in Polish and English. Results. The review of articles concerning the treatment of anxiety disorders clearly suggests that propranolol is effective in reducing the frequency of panic attacks and the tendency for avoidance behavior in patients with agoraphobia. Other studies report on potential benefits in terms of early interventional prevention and treating posttraumatic stress disorder with propranolol. However, there is lack of randomized clinical trials concerning the therapeutic effect of other adrenolytic drugs in treating anxiety disorders. Early research works reported that (mainly lipophilic) beta blockers may have a depressogenic effect; however, the latest studies have not confirmed it. Conclusions. The contemporary research on the therapeutic potential of beta blockers in treating anxiety disorders is insufficient. What seems to be most promising, however, are reports concerning the desirable effects of using adrenolytic drugs in treating posttraumatic stress disorder, which implicates the necessity of conducting further research verifying the validity of their application.